Fairness, legitimacy and the regulation of home-sharing platforms - Newlands, Gemma; Lutz, Christoph (International journal of contemporary hospitality management, 2020)
Purpose The purpose of this study is to contribute to current hospitality and tourism research on the sharing economy by studying the under-researched aspects of regulatory desirability, moral legitimacy and fairness in the context of home-sharing platforms (e.g. Airbnb). Design/methodology/approach Three separate 2×1 between-subjects experimental vignette surveys are used to test the effects of three types of fairness (procedural, interpersonal and informational) on two outcomes: moral legitimacy and regulatory desirability. Findings The results of the research show that high perceived fairness across all three types increases moral legitimacy and reduces regulatory desirability. Respondents who perceive a fictional home-sharing platform to be fair consider it to be more legitimate and want it to be less regulated. Research limitations/implications Following established practices and reducing external validity, the study uses a fictional scenario and a fictional company for the experimental vignette. The data collection took place in the UK, prohibiting cultural comparisons. Practical implications The research is useful for home-sharing platform managers by showing how they can boost moral legitimacy and decrease regulatory desirability through a strong focus on fairness. It can also help policymakers and consumer protection advocates by providing evidence about regulatory desirability and how it is affected by fairness perceptions. Originality/value The study adds to hospitality and tourism research by offering theoretically meaningful and practically relevant conclusions about the importance of fairness in driving stakeholder opinions about home-sharing platforms.